Categorical data analysis using SPSS for periodontology - Wan Ahmad, Wan Muhamad Amir; Mohd Ibrahim, Mohamad Shafiq; Min, Nasar Um; Yaqoob, Muhammad Azeem (Penerbit Universiti Sains Malaysia, 2019)
Statistics is a very powerful tool for data measurement. It can give meaning to meaningless numbers. On the basis, data can be classified as categorical or continuous. This book focuses on categorical data analysis. Categorical data classifies an observation to one or more categories. To get a clear understanding on how to analyze categorical data, this book emphasizes on categorical data analysis, especially for all beginners among dental students, dental researchers and dental lecturers. It is a compulsory method of analysis that researchers should learn, as it provides core skills that will be very useful for conducting categorical data analysis. Besides that, this book gives the researchers an idea on how to design a study that will optimize the output of the research study.